Religion, rituals, and folklore a cultural overview of the Lagunenses - Gotiangco, Jr. li, Gil G. (2004)
Colorful, interesting, and intriguing are but a few ways of characterizing Laguna's cultural past. From prehistoric times to the twenty-first century, the Lagunenses continually captivate people's attention with its rich collection of folklore, amusing religious traditions, persistent beliefs/perceptions, and alluring verbalizations of everyday life. Physical evidences and oral testimonies highlight a significant interplay of naturalistic, materialistic, and spiritual scenarios that eventually evolved into present day Lagunense way of life. This paper is not intended to provide a comprehensive picture of Laguna's cultural world. It is primarily meant to project a long cultural tradition that persistently draws awe and amusement. At times, empiricism provides explanations but, as social scientists often note, positivist approaches to cultural experiences may not be sufficient. Needless to emphasize, as the other conference papers will probably epitomize, there is more to explore, to understand, and to savor Philippine cultural traditions.
Includes bibliographical references (pages 255-258).